Benjamin and Dewey on Aesthetic Experience. A Possible Dialogue (ALPHA. Journal of Arts, Literature and Philosophy, 2024)
This article explores the connections that can be established between Walter Benjamin's aesthetic theory and John Dewey's aesthetic theory. To make this comparison, we first analyze Dewey's approach to the notion of aesthetic experience as a way of reconnecting the realm of art with everyday life, and then we study different texts by Walter Benjamin in which he suggests a form of aesthetic experience based on avant-garde art. This work hypothesizes that in both authors the notion of aesthetic experience is understood similarly and answers common problems concerning the place of art in the modern world.
Keywords: Benjamin; Dewey; Aesthetics; Experience; Critical theory; Pragmatism